(untitled) (VETERINARIA, 2020)
This study was conducted on 240 samples, 80 muscle, 80 kidney and 80 liver samples, which were collected from 80 calves carcasses (between 1-3 years old) from Western Syria (Latakia, Tartus, Jableh and Safita). Samples were analyzed for the arsenic contamination using Atomic Absorption Spectrometry (AAS). The results showed that concentrations of arsenic in the kidney, liver and muscle of the calves in Latakia region were 0.7175, 0.602 and 0.4715 mg/kg, respectively. In Jableh region they were 0.43, 0.3425 and 0.2665 mg/kg, respectively, in Tartus region 0.5035, 0.4545 and 0.2918 mg/kg, respectively, and in Safita region 0.3615, 0.342 and 0.2168 mg/kg, respectively. Results also revealed that the highest arsenic concentration was detected in the kidney followed by liver and muscle, and was higher in the samples from Latakia and Tartus regions compared to the samples from Jableh and Safita regions.